2019
DOI: 10.1103/physrevapplied.11.014061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meissner Screening and Trapped Magnetic Flux on Magnetization Dynamics in Thick Nb/Ni80Fe20/Nb Trilayers

Abstract: We investigate the influence of Meissner screening and trapped magnetic flux on magnetization dynamics for a Ni80Fe20 film sandwiched between two thick Nb layers (100 nm) using broadband (5-20 GHz) ferromagnetic resonance (FMR) spectroscopy. Below the superconducting transition Tc of Nb, significant zerofrequency line broadening (5-6 mT) and DC resonance field shift (50 mT) to a low field are both observed if the Nb thickness is comparable to the London penetration depth of Nb films (≥ 100 nm). We attribute th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 44 publications
2
64
3
1
Order By: Relevance
“…This sample is referred to as S1. Thickness of the Py layer is selected for a direct comparison of the obtained results with previous research studies [20,21]. Fig.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…This sample is referred to as S1. Thickness of the Py layer is selected for a direct comparison of the obtained results with previous research studies [20,21]. Fig.…”
Section: Methodsmentioning
confidence: 98%
“…In Refs. [20] and [21] a drastic increase of the ferromagnetic resonance frequency has been observed in superconductor-ferromagnet-superconductor three layers in the presence of superconducting proximity between superconducting and ferromagnetic layers. The origin of the phenomenon remains unclear.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In such systems charge and (non-collinear) spin transport are closely linked and need to be treated on the same footing. Recently there has also been increased interest to couple superconductors to magnets and find out how superconductivity affects the magnetization dynamics, [5][6][7][8][9][10][11][12][13][14][15] including thermally driven effects [16]. On the other hand, recent work has shown that a combination of magnetic and superconducting systems results to giant thermoelectric effects [17][18][19][20] coupling charge and heat currents.…”
mentioning
confidence: 99%